Sekali Pendatang Tetap “Pendatang”? Menyibak Sekat “Pribumi-Nonpribumi” di Indonesia - Virgenius, Charles; Sinaga, Henri Damian (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2017)
Identification of a group of people does not come out of the blue. There is a long history and a lengthy process which makes a group identity comes up. In Indonesia, the ethnic Chinese, formerly called ‘orang-orang non-pribumi’ (nonnatives, immigrants), are one of many groups of people with their ambiguous identity. Such ambiguity of the ethnic Chinese remains so up to the present day, even though the term ‘Cina’ has been altered into ‘Tionghoa’’.Their presence has been considered as ‘the others’ amidst the people of the country and their identity as ‘immigrants’ has been perpetuated. Nobody knows when such stigma will be over. Although they have been in the country for generations, their status as ‘immigrants’ seems unchanged. The article tries to explore the background of the natives-immigrants stereotype and the discourse on ethnic Chinese identity in the post-Soeharto era.